1998
DOI: 10.1182/blood.v92.11.4150
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Inhibits the Development of Dendritic Cells and Dramatically Affects the Differentiation of Multiple Hematopoietic Lineages In Vivo

Abstract: Defective function of dendritic cells (DC) in cancer has been recently described and may represent one of the mechanisms of tumor evasion from immune system control. We have previously shown in vitro that vascular endothelial growth factor (VEGF), produced by almost all tumors, is one of the tumor-derived factors responsible for the defective function of these cells. In this study, we investigated whether in vivo infusion of recombinant VEGF could reproduce the observed DC dysfunction. Continuous VEGF infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
131
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 809 publications
(134 citation statements)
references
References 47 publications
3
131
0
Order By: Relevance
“…This is consistent with the previously observed reduction of CD1a+ Langerhans cells at the edge of venous leg ulcers 21 . The variation in CD1a+ cell numbers may reflect differences in the recruitment capacities in various microenvironments, possibly based on the expression of molecules responsible for Langerhans cell trafficking into the skin 22,23 or influencing Langerhans cell differentiation 24,25 . Langerhans cells are localized in the epidermis where surrounding keratinocytes produce a number of cytokines and growth factors influencing Langerhans cells 26 .…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the previously observed reduction of CD1a+ Langerhans cells at the edge of venous leg ulcers 21 . The variation in CD1a+ cell numbers may reflect differences in the recruitment capacities in various microenvironments, possibly based on the expression of molecules responsible for Langerhans cell trafficking into the skin 22,23 or influencing Langerhans cell differentiation 24,25 . Langerhans cells are localized in the epidermis where surrounding keratinocytes produce a number of cytokines and growth factors influencing Langerhans cells 26 .…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that VEGF can enhance the phosphorylation of Erk1/2, but not those of p38MAPK or Akt in mDCs . Moreover, our results and those from other groups showed that VEGF can impair the immune function through the NF‐κB pathway . From these results, it could be inferred that the molecular targets of VEGF to mDCs were COF1, Erk1 and 2, and NF‐κB, all of which are related to the cytoskeleton, motility, and gene transcription.…”
Section: Discussionsupporting
confidence: 61%
“…As shown in Figures and , the motility of mDCs was impaired by VEGF through the VEGFR2‐RhoA‐COF1 pathway. Several groups have shown that VEGFR1 is the major mediator of VEGF effects on the NF‐κB pathway in hematopoietic stem cells and that VEGF affects the early stage of myeloid/DC differentiation . Clauss et al showed that VEGFR1 is biologically active in monocytes/macrophages and that VEGF stimulates the migration and chemotaxis of human monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies established the concept that experimentally induced TAA‐specific immunity is a rational and potentially efficacious means to treat cancer, including ovarian cancer. Nonetheless, recent work demonstrates that lack of naturally induced TAA‐specific immunity is not simply a passive process 5–12 . We discuss recent data clearly demonstrating that ‘tumors actively prevent induction of TAA‐specific immunity through induction of TAA‐specific tolerance’ 13 .…”
mentioning
confidence: 96%